Macrofaunal Assemblages on Oyster Aquaculture and Rock Reef Habitat in Long Island Sound. (6th November 2019) - Mercaldo‐Allen, Renee; Clark, Paul; Liu, Yuan; Meseck, Shannon; Milke, Lisa; Redman, Dylan
Abstract: Trap sampling was used to survey the relative abundance of juvenile fish and invertebrates near three habitats including an off‐bottom oyster cage farm (cage farm), a traditional on‐bottom oyster culture area (shell bottom), and a natural cobble and boulder reef (rock reef) in a coastal embayment in Long Island Sound near Milford, Connecticut. Ten traps, deployed on two subsites within each habitat (20/habitat), were allowed to soak for ~24 hours, two to three times per week, from June through September 2016. The assemblages of juvenile finfish appeared to be similar on the cage farm and rock reef, while the composition of the invertebrate community was more variable among the three habitats. These preliminary observations suggest that oyster cage farms may provide functional habitat that is populated by structure‐oriented finfish communities similar to those that are found on natural rock reefs in Long Island Sound.